Modeling 'Candidatus Liberibacter asiaticus' Movement Within Citrus Plants - Raiol-Junior, Laudecir L. [UNESP]; Cifuentes-Arenas, Juan C. [UNESP]; Cunniffe, Nik J.; Turgeon, Robert; Lopes, Silvio A. (Amer Phytopathological Soc, 2021)
The phloem-limited 'Candidatus Liberibacter asiaticus' (Las) causes huanglongbing, a destructive citrus disease. Graft-inoculated potted plants were used to assess Las speed of movement in phloem in the greenhouse, and the impacts of temperature on plant colonization in growth-chamber experiments. For assessment of Las speed, plants were inoculated at the main stem and assessed over time by quantitative PCR (qPCR) or symptoms at various distances from the inoculum. For colonization, the plants were inoculated in one of two opposite top branches, maintained at from 8 to 20 degrees C, from 18 to 30 degrees C, or from 24 to 38 degrees C daily range, and assessed by qPCR of samples taken from noninoculated shoots. For all experiments, frequencies of Las-positive sites were submitted to analysis of variance and binomial generalized linear model and logistic regression analyses. Probabilities of detecting Las in greenhouse plants were functions of time and distance from the inoculation site, which resulted in 2.9 and 3.8 cm day(-1) average speed of movement. In growth chambers, the temperature impacted plant colonization by Las, new shoot emission, and symptom expression. After a 7-month exposure time, Las was absent in all new shoots in the cooler environment (average three per plant), and present in 70% at the milder environment (six shoots, severe symptoms) and 25% in the warmer environment (eight shoots, no visible symptoms). Temperature of 25.7 degrees C was the optimum condition for plant colonization. This explains the higher impact and incidence of huanglongbing disease during the winter months or regions of milder climates in Brazil.
Keywords: bacterial disease; Citrus spp.; huanglongbing; qPCR